2016
DOI: 10.1002/stem.2280
|View full text |Cite
|
Sign up to set email alerts
|

Adenosinergic Immunosuppression by Human Mesenchymal Stromal Cells Requires Co-Operation with T cells

Abstract: Mesenchymal stem/stromal cells (MSCs) have the capacity to counteract excessive inflammatory responses. MSCs possess a range of immunomodulatory mechanisms, which can be deployed in response to signals in a particular environment and in concert with other immune cells. One immunosuppressive mechanism, not so well-known in MSCs, is mediated via adenosinergic pathway by ectonucleotidases CD73 and CD39. In this study, we demonstrate that adenosine is actively produced from adenosine 5 0 -monophosphate (AMP) by CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 40 publications
5
85
3
1
Order By: Relevance
“…Adding a parenthesis to this subject, CD39 expression by MSCs has been subject to conflicting observations [177]. In contrast to our observations [175] and others [178,179], some authors describe a lack or low CD39 expression by MSCs [176,180]. In our view, this might be due to specific experiment design or to antibody variation.…”
Section: Mscs and Adenosinecontrasting
confidence: 92%
See 1 more Smart Citation
“…Adding a parenthesis to this subject, CD39 expression by MSCs has been subject to conflicting observations [177]. In contrast to our observations [175] and others [178,179], some authors describe a lack or low CD39 expression by MSCs [176,180]. In our view, this might be due to specific experiment design or to antibody variation.…”
Section: Mscs and Adenosinecontrasting
confidence: 92%
“…The fact that T-cells also express CD39 may not exclude the possibility of MSCs and T-cell cooperation for the production of adenosine, in which highly CD39 expressing activated Tcells may break ATP into ADP and then AMP, which is used by CD73 expressing MSCs to obtain adenosine. This hypothesis, first discussed by our group, has indeed been confirmed experimentally by Kerkelä et al [176], in 2016. Adding a parenthesis to this subject, CD39 expression by MSCs has been subject to conflicting observations [177].…”
Section: Mscs and Adenosinesupporting
confidence: 79%
“…The ability of CeCa-MSCs to catalyze the ATP, ADP and AMP nucleotides and to generate immunosuppressive Ado suggests that CeCa-MSCs are part of a non-hematopoietic cell population that can significantly contribute to the generation of an immunosuppressive microenvironment. The high CD39 and CD73 expression found in CeCa-MSCs contrasts with results obtained by Saldanha-Araujo et al [23] and Kerkelä et al [24], who reported that both BM-MSCs and UCB-MSCs express high levels of CD73 and low levels of CD39 on their surface, enabling them to quickly generate Ado from AMP but not from ATP. However, both studies showed that the addition of activated T-cells to their culture system allowed the generation of Ado from ATP due to the high CD39 expression on activated T-cells, suggesting a co-operative functional activity between MSCs and activated T-cells in the inflammatory microenvironment to generate Ado from ATP released in the damaged tissue [23, 24].…”
Section: Discussioncontrasting
confidence: 76%
“…Recently, have been reported that MSCs derived from either bone marrow (BM-MSCs) or umbilical cord blood (UCB-MSCs), may suppress the response of T lymphocytes through the purinergic pathway [23, 24]. In this pathway, nucleotides (ATP and ADP) released by a variety of cell types in response to stress signals such as injury, hypoxia and inflammation, which commonly occur in the tumor microenvironment, are jointly hydrolyzed by CD39 ectoenzyme (ENTPD1, ectonucleoside triphosphate diphosphohydrolase-1, EC 3.6.1.5) to generate the respective nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…In total, three biological replicates were measured from each sample. The data were analysed using NTA software 3.0 with the detection threshold 5 [14]. …”
Section: Methodsmentioning
confidence: 99%